Functionally distinct NPAS4-expressing somatostatin interneuron ensembles critical for motor skill learning - Yang, Jungwoo; Serrano, Pablo; Yin, Xuming; Sun, Xiaochen; Lin, Yingxi; Chen, Simon X. (Neuron (Cambridge, Mass.), 2022)
During motor learning, dendritic spines on pyramidal neurons (PNs) in the primary motor cortex (M1) undergo reorganization. Intriguingly, the inhibition from local somatostatin-expressing inhibitory neurons (SST-INs) plays an important role in regulating the PN plasticity and thus new motor skill acquisition. However, the molecular mechanisms underlying this process remain unclear. Here, we identified that the early-response transcription factor, NPAS4, is selectively expressed in SST-INs during motor learning. By utilizing in vivo two-photon imaging in mice, we found that cell-type-specific deletion of Npas4 in M1 disrupted learning-induced spine reorganization among PNs and impaired motor learning. In addition, NPAS4-expressing SST-INs exhibited lower neuronal activity during task-related movements, and chemogenetically increasing the activity of NPAS4-expressing ensembles was sufficient to mimic the effects of Npas4 deletion. Together, our results reveal an instructive role of NPAS4-expressing SST-INs in modulating the inhibition to downstream task-related PNs to allow proper spine reorganization that is critical for motor learning. •Motor learning selectively induces NPAS4 expression in SST-INs in M1•Cell-type specific KO of Npas4 in SST-INs of M1 in mice impairs motor learning•NPAS4+ SST-INs exhibited lower activity during task-related movements•NPAS4 re-expression maintains the functionally distinct SST-INs throughout learning Utilizing in vivo two-photon imaging in behaving mice, Yang et al. reveal that motor learning triggers an emergence of an NPAS4-expressing SST-IN ensemble that regulates the spine remodeling of downstream PNs through disinhibition. Moreover, NPAS4 re-expression is critical in maintaining the functionally distinct SST-IN ensemble throughout the course of learning.